To Study The Problems Faced By The Design Institutes While Creating Multi-Purpose Areas - Adil, Afroz; Soni, Gunja; Bhatore, Vijeta (Journal of Neonatal Surgery, 2025)
India is a fast-developing country, where villages are growing into towns, towns into cities and cities into metro cities. The population is also increasing at a very fast rate. Youth for its development, education and better job opportunities is moving towards urban areas. As the youth are moving towards cities for their betterment, they are in constant search of upgrading their education and knowledge. For this many schools, colleges and universities are being constructed to fulfill the growing demand. So, this shifting from rural to urban is leading to space crisis. Everything in this world is designed be it a home, an article, an outfit, or a website. The art of designing is leading to more design colleges in the urban areas. Limited accessible land and increasing demand for more design institutes leads to an imbalance of available amenities as referred by UGC (University Grants Commission), AICTE (All India Council of Technical Education), and COA (Council of Architecture). Colleges in the cities are build but lack certain amenities or facilities that are a must have as per UGC, AICTE, and COA [14,15]. To overcome this many design institutes, opt for multipurpose areas in their premises which when needed can be utilized as per the current requirement. The design institutes while using these multi-purpose spaces face certain problems in their day-to-day execution. This study is done to understand such problems that the design institutes face. For the accomplishment of this study schedule and interview was conducted and data thus obtained was collected and analyzed